2017
DOI: 10.1177/1053825917700922
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits of Service Learning: A Comparison of Collegiate Recreation Concentrations

Abstract: Service learning is becoming a more utilized method of instruction in collegiate settings, and holds the potential to provide a deeper, more transferable meaning of course material for students. The purpose of this research was to examine if therapeutic recreation (TR) concentration students perceived service learning to be more personally and academically beneficial than non-TR concentrations in a collegiate recreation program. Undergraduate and graduate students in a recreation program at a regional, America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Reflection in service-learning means that these projects allow for the construction of knowledge (Fisher, Sharp & Bradley, 2017). Reflection differentiates service-learning from other forms of experiential education as it specifically connects the service experience to desired learning outcomes.…”
Section: The Rise Of "Real Democracy"mentioning
confidence: 99%
See 1 more Smart Citation
“…Reflection in service-learning means that these projects allow for the construction of knowledge (Fisher, Sharp & Bradley, 2017). Reflection differentiates service-learning from other forms of experiential education as it specifically connects the service experience to desired learning outcomes.…”
Section: The Rise Of "Real Democracy"mentioning
confidence: 99%
“…Thus, individual needs should be identified and addressed so that students are not negatively impacted by the experience (Larsen, 2017). Poor design can also reinforce students' existing paternalistic and stereotypical ideas of community members as being deficient and them (students) acting as community savior (Chupp & Joseph, 2010;Fisher et al, 2017). Proper design can elicit positive emotions as well as increased positive outcomes overall (Chupp & Joseph, 2010).…”
Section: The Rise Of "Real Democracy"mentioning
confidence: 99%
“…Prior research reported the personal and academic benefits (Fisher et al, 2017) of short-term service assignment in students within different professions. For instance, in medical students and residents, service trips have been shown to be constructive in creating insight into ethical and societal issues regarding global health (Abedini et al, 2012) while creating valuable experiences for professional development (Chetta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…With this renewed visibility, service-learning began appearing more frequently as a requirement in credit-bearing courses, a pedagogical shift not initially garnering universal support. Some faculty were reluctant to try the new pedagogy “due to the large amount of time investment required to make it effective” (Fisher, Sharp, & Bradley, 2017, p. 188); others were skeptical of its educational value, viewing it as merely “fluffy, feel-good stuff” (Markus, Howard, & King, 1993, p. 411).…”
Section: Historical Traditionsmentioning
confidence: 99%